Perencanaan Model Bisnis pada Startup “PaperQ” menggunakan Metode Business Model Canvas - Puteri Johar Aunillah; Retno Waluyo; Argiyan Dwi Pritama (STMIK Banjarbaru, 2022)
Students as people who are in a higher education environment are usually required to carry out scientific activities such as writing scientific papers. However, in reality, many students experience difficulties while working on scientific papers. This opens up business opportunities for the “PaperQ” startup as a technology-based startup that provides scientific writing consulting services to overcome the difficulties experienced by these students. The purpose of this study is to plan a startup business model